IMPLEMENTASI KEBIJAKAN SATUANPOLISI PAMONG PRAJA BERDASARKAN PERATURAN DAERAH KABUPATEN SUMBAWA BARAT NOMOR 2 TAHUN 2019 TENTANG PENERTIBAN HEWAN TERNAK - ALIMUDDIN, ALIMUDDIN; YAMIN, AHMAD; GUNAWAN, JASARDI (Universitas Mahasaraswati K. Mataram, 2024)
The aims of this study are 1) To describe the implementation of the Civil Service Police Unit policy based on Regional Regulation Number 2 of 2019 concerning Control of Livestock (Case Study in Office Environments (KTC) Taliwang District, West Sumbawa Regency). 2) To describe the supporting factors and obstacles to the implementation of the Civil Service Police Unit policy based on Regional Regulation Number 2 of 2019 concerning Controlling Livestock (Case Study in Office Environments (KTC) Taliwang District, West Sumbawa Regency). This study used descriptive research with a qualitative approach, data collection techniques through interviews, observation and documentation, with district chiefs Taliwangas key informants. The results of the research show that implementing a policy is in the form of: communication, resources, disposition and organizational structure. Supporting and inhibiting factors are social media which is one of the supporting factors for the success of this policy, namely through the Taliwang District Instagram and West Sumbawa news Instagram, with these media it will certainly make socialization easier and can also be a means of receiving public complaints regarding the Sumbawa Regency Regional Regulation West No. 2 of 2019 concerning Control of Livestock. Inhibiting factors are lack of public awareness, lack of facilities and infrastructure and lack of apparatus resources. Thus it can be concluded that implementing a policy is in the form of: communication, resources, disposition and organizational structure. Supporting factors are easily accessible communication media while inhibiting factors are lack of awareness, lack of facilities and lack of human resources.